Implementation of acts of interstate associations in the national legal systems of the Republic of Belarus and the Russian Federation: existing mechanisms and improvement of legal regulation - Vasilevich, Grigorii A.; Kashirkina, Anna A.; Morozov, Andrei N. (Journal of the Belarusian State University. Law, 2019)
The article examines issues related to the fulfillment of international obligations, the adoption of the Republic of Belarus and the Russian Federation in the framework of interstate integration associations, based on the analysis of international and domestic regulatory legal acts. According to the results of studies of international legal acts, legislative acts of the Republic of Belarus and the Russian Federation, as well as scientific developments, proposals were made to improve legislation in the area of fulfilling international obligations, including within international organizations, including the Eurasian Economic Union.
Keywords: Republic of Belarus; Russian Federation; interstate integration associations; Eurasian Economic Union; international treaties; decisions; international obligations; implementation